(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the assessment of stops during nesting, wintering and molting, as well as during migration, as key ornithological areas for the protection of rare and endangered birds. The assignment of the status of a protected natural area to the main ornithological territories of the Fergana Valley and their significance in preserving populations of rare and endangered bird species in Uzbekistan are also analyzed.